Fall cultivar of rapeseed (Brassica napus) for reduction of damage due to late season drought - A H, SHIRANI RAD; N, SHAHSAVARI; M, JAIS H; A, DADRASNIA; A, ASKARI; M, SALJUGHI (The Indian Journal of Agricultural Sciences, 2015)
This study examined the possibility of cultivating the spring cultivars of rapeseed in the cold temperate regions during Fall season. The objective was to ensure early ripening, avoid drought and even reduce sun exposure during the final growing stages. This was with the Spring cultivation of the same cultivars. Experiment was carried out over two years. Planting season was the main factor which included two entities, namely “planting in Fall” (September 25) and “planting in Spring” (March 25). Plant cultivar was the sub factor which includes 24 cultivars of rapeseed. Effects of the planting season and cultivar, as well as the interaction of both on grain and oil yields, were significant (P<0.01). In the Fall planting season, Hyola 401 hybrid had the highest grain yield and Hyola 330 hybrid had the highest oil yield. However, in the spring planting season, RG 405.03 cultivar had the highest grain and oil yields. The study indicated that it was possible to cultivate the spring cultivars of the plant in cool temperate regions during Fall season.